Optical three-dimensional displacement measurement based on moiré methodology and its application to space structures. (January 2022) - Ri, Shien; Yoshida, Takeshi; Tsuda, Hiroshi; Sato, Eiichi
Highlights: An accurate optical three-dimensional displacement measurement method is proposed The proposed calibration method can eliminate error due to the tile angle of the camera The developed method is useful for inspection in the space structures Abstract: Optical methods providing full-field deformation information is of interest to mechanical engineers. In this study, an accurate optical three-dimensional displacement measurement method using a single camera attached to a precision 3-axis moving stage was developed. This paper presents the fundamental measurement principle and experiments for validating the measurement accuracy. The in-plane and out-of-plane displacements are simultaneously determined by calculating the phase difference and the phase gradient difference of the moiré fringe before and after deformation. The developed method was applied to displacement measurement in a loading test of a carbon fiber reinforced plastics (CFRP) cylindrical payload 2.5 m in diameter and 2.0 m long used in a solid rocket. The three-dimensional displacement results obtained from the developed method showed a good agreement with those measured with the extensometers conventionally employed in the displacement measurement. The developed method is useful for inspection in the space field and to secure the health monitoring of large-scale structures.